2001
DOI: 10.1002/ijc.1573
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of reproductive and hormonal factors in thyroid cancer: Evidence from a case‐control study in the Middle East

Abstract: Thyroid cancer is the second most common neoplasm among women in Kuwait and several other countries in the Middle East. Most of these countries also have relatively high birth and total fertility rates. To examine potential relationships between reproductive and hormonal factors and thyroid cancer, we conducted a population-based case-control interview study among 238 women diagnosed with thyroid cancer and a similar number of individually matched controls in Kuwait. Among the demographic variables, women with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 30 publications
2
42
0
2
Order By: Relevance
“…This is perhaps the first indication in the literature of a possible link between history of post-partum thyroiditis and thyroid cancer. The finding has been discussed in a separate paper (Memon et al, 2002). Overall, individuals with a history of any benign thyroid disease were at a considerably high risk of developing thyroid cancer (OR=6.4; 95% CI: 3.4 -12.0).…”
Section: Benign Thyroid Diseasementioning
confidence: 90%
See 1 more Smart Citation
“…This is perhaps the first indication in the literature of a possible link between history of post-partum thyroiditis and thyroid cancer. The finding has been discussed in a separate paper (Memon et al, 2002). Overall, individuals with a history of any benign thyroid disease were at a considerably high risk of developing thyroid cancer (OR=6.4; 95% CI: 3.4 -12.0).…”
Section: Benign Thyroid Diseasementioning
confidence: 90%
“…The study population and methods are described in detail elsewhere (Memon et al, 2002). Briefly, our study was conducted at the Kuwait Cancer Control Centre (KCCC) which is the only specialised cancer treatment and follow-up hospital in the country.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size found varied from 99 to 749 subjects except for one study conducted in Oman in which 36000 babies were diagnosed. The study population of these studies comprised of children of school age and adults: five studies were case control with sample size varying from 100 to 313 subjects (Akbar et al, 2006;Memon et al, 2002aMemon et al, , b, 2004Memon et al, , 2010; four of the studies were from Kuwait (Memon et al, 2002a(Memon et al, , b, 2004Memon et al, 2010); and one from Saudi Arab (Akbar et al, 2006) and the study population was recruited from hospitals in Kuwait and Saudi Arab, retrospectively, and eight studies were retrospective; three were from Yemenone from Iraq (Nasheiti, 2005), three from Saudi Arab and one from United Arab Emirate. The sample size was found to vary from 45 to 810 subjects and comprised of children and adults, and all data collected were hospital based.…”
Section: Methodsmentioning
confidence: 99%
“…(14) but recent studies reported that the use of hormonal therapy of fertility drugs are not associated with thyroid malignancy. (18,19) The availability of more sensitive and better diagnostic tools may be responsible for the increasing incidence of thyroid cancer.…”
Section: Resultsmentioning
confidence: 99%